Non-linear relationship between the first meal time of the day and gallstone incidence in American adults: a population-based cross-sectional study - Sun, Tiange; Zhang, Lidong; Lu, Ying; Zhang, Xianwen; Cui, Jinhao; Yang, Tongheng; Zhang, Dan; Zheng, Bowen; Zheng, Shuguo (Frontiers in Nutrition, 2024)
BackgroundIrregular meal time is associated with gallstones. The time–dose effect between meal time and gallstone formation remains unknown.ObjectiveThis study aimed to investigate the association between the first meal time (FMT) of the day and the prevalence of gallstones.MethodsBased on data from the National Health and Nutrition Examination Survey from 2017 to March 2020, the associations between the FMT of the day and the prevalence of gallstones were analyzed via multivariable logistic regression, restricted cubic spline curves, subgroup analysis, and interaction tests.ResultsA total of 6,547 participants were included. The fully adjusted model indicated a positive correlation between the FMT of the day and the prevalence of gallstones (odds ratio [OR] = 1.05, 95% confidence interval [CI] = 1.02 ~ 1.08); this association was consistent across subgroups. The risk of developing gallstones was the greatest when the FMT was between 09:00 and 14:00 (OR [95% CI] = 1.49 [1.24 ~ 1.77]). There was a non-linear relationship between the FMT and gallstone incidence (P for non-linearity = 0.042), with an inflection point at 13.4 h. After the 13.4-h mark, the risk of developing gallstones did not increase further.ConclusionThe FMT of the day is positively correlated with the prevalence of gallstones, and there is a non-linear relationship and threshold effect between the two. Skipping breakfast is associated with a greater risk of developing gallstones. This study provides new evidence for the dietary prevention of gallstones.